2015
DOI: 10.1002/2015jf003641
|View full text |Cite
|
Sign up to set email alerts
|

Tidal and seasonal variations in calving flux observed with passive seismology

Abstract: The seismic signatures of calving events, i.e., calving icequakes, offer an opportunity to examine calving variability with greater precision than is available with other methods. Here using observations from Yahtse Glacier, Alaska, we describe methods to detect, locate, and characterize calving icequakes. We combine these icequake records with a coincident, manually generated record of observed calving events to develop and validate a statistical model through which we can infer iceberg sizes from the propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
48
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(68 citation statements)
references
References 74 publications
16
48
2
Order By: Relevance
“…These two factors reach a critical point in October, leading to a full-width terminus retreat of ∼80 m ( Figure 9A). Bartholomaus et al (2015b) observed that Yahtse's calving flux peaks in the fall, coincident with the timing of the full-width terminus retreat observed here. Seasonal terminus retreat at Yahtse shows a dependence on tidewater glacier dynamics governing seasonal changes in ice flux (e.g., Stearns et al, 2015) as well as submarine melting and calving flux (e.g., Bartholomaus et al, 2015b).…”
Section: Seasonal Dynamicssupporting
confidence: 80%
See 1 more Smart Citation
“…These two factors reach a critical point in October, leading to a full-width terminus retreat of ∼80 m ( Figure 9A). Bartholomaus et al (2015b) observed that Yahtse's calving flux peaks in the fall, coincident with the timing of the full-width terminus retreat observed here. Seasonal terminus retreat at Yahtse shows a dependence on tidewater glacier dynamics governing seasonal changes in ice flux (e.g., Stearns et al, 2015) as well as submarine melting and calving flux (e.g., Bartholomaus et al, 2015b).…”
Section: Seasonal Dynamicssupporting
confidence: 80%
“…Bartholomaus et al (2015b) observed that Yahtse's calving flux peaks in the fall, coincident with the timing of the full-width terminus retreat observed here. Seasonal terminus retreat at Yahtse shows a dependence on tidewater glacier dynamics governing seasonal changes in ice flux (e.g., Stearns et al, 2015) as well as submarine melting and calving flux (e.g., Bartholomaus et al, 2015b). We interpret that the terminus retreats from the crest of its submarine moraine, which would result in a loss of backstress that could cause the winter acceleration.…”
Section: Seasonal Dynamicssupporting
confidence: 80%
“…This relationship is strictly empirical, because signal attenuation as well as site‐related signal‐to‐noise ratio and local amplification effects do not allow application to other calving fronts and different source station distances. A similar relationship between T and V was later confirmed by observations on the same glacier by O'Neel et al [], on Yahtse Glacier (Alaska, USA) by Bartholomaus et al [] and on the Arctic archipelago of Svalbard (Norway) (A. Köhler and C. Nuth, personal communication, 2016).…”
Section: Seismic Source Processessupporting
confidence: 65%
“…Seismic monitoring revealed that calving mass loss depends on ocean tides and terminus geometry [ O'Neel et al , ; Walter et al , ; Bartholomaus et al , ; Koubova , ]. Recently, Köhler et al [] analyzed 14 year period (2000–2013) of seismicity on Spitsbergen and observed a high number of icequakes (1–8 Hz) associated with tidewater calving glaciers.…”
Section: Seismic Source Processesmentioning
confidence: 99%
See 1 more Smart Citation